Analisis Penerapan Sistem E-Commerce Pada Warmindo Abang Adek Di Jakarta Barat - Regina Rizky Amaliah; Widiyono Widiyono; Anita Maulina (JAMBIS : Jurnal Administrasi Bisnis, 2021)
In the current technology, there is a competition between traditional business have contributed to developing its effort through technology. The growing competition among small businesses pushes each traditional entrepreneur and implementing online sales to the current businesses listed. The purpose of this research is to know and analyze how the practices of the e-commerce system, constraints in the application of the e-commerce system, and find out what is the solution to overcoming obstacles to the Warmindo Abang Adek Jakarta. The method used by researchers is an in-depth interview method of business owners Warmindo Abang Adek Jakarta. Based on the results of the research, the e-commerce application on Warmindo Abang Adek Jakarta concurs with e-commerce and conventionally. The application of e-commerce has a contributing role in sales volume and competition. Therefore, Warmindo Abang Adek Jakarta has been listed as a go-food partner since 2016 which was the first known to the public, but the owners don’t understand the e-commerce system. forasmuch any online business or place will run smoothly if the owner understands the cooperation current system. From this research, it can be known that it’s important to overcome obstacles to Warmindo Abang Adek efforts. Optimizing online sales by using an application system to boost sale and evaluate online sales strategies must keep goingKeywords: Green Marketing; Consumer Behaviour; Brand Image